Decolourization of Novacron Blue and Novacron Super Black Azo Dyes by Bacillus spp Isolated from Textile Effluents in Bangladesh - Mahbub, K. R.; Morium, B.; Ahmed, M. M.; Akond, M. A.; Andrews, S. (Journal of Scientific Research, 2015)
Effluents containing azo dyes from textile and dyeing industries cause serious pollution to aquatic environments. In this study, azo dye decolourization potential of five bacterial isolates was examined in different physicochemical conditions such as pH, temperature and glucose concentrations. Based on biochemical characteristics the isolates were identified as Bacillus badius (isolate A3 and A4) and Bacillus sphaericus (isolate A5, B8, C5). These bacteria showed decolourization of two experimental azo dyes, Novacron Blue and Novacron Super Black at different temperatures, pH and glucose concentrations up to 92% after 72 h of incubation. Decolourization increased with time and temperature. Neutral to alkaline pH with increased concentration of glucose facilitated dye removal. The maximum decolourization (92%) of experimental dyes was observed at 35°C, pH 7-8 with 2% glucose. Bacillus badius demonstrated better decolourization.